PERDAGANGAN BURUNG-BURUNG PARUH BENGKOK DI BALI [Parrot Trade in Bali] - W Widodo (The East Java Biological Society, 2005)
The survey was carried out to know some aspects of the bird trade in Bali on May 2002, especially to observe the diversity and abundance of species of Psittacidae Family along with their problems. The survey was done by direct observations and interview to the traders in the Sanglah and Satria Bird Markets, Denpasar-Bali. The total of 80 spescies of birds was traded in Bali and most of them i.e.: 75 species or 1577 individuals were found in the Satria bird market, but only 37 species or 393 individuals traded in the Sanglah bird market. Psittacidae family was found more abundantly, i.e.: 428 individiuals in 13 species of parrots. Those spesies of parrots were: Violet-necked Lory (Eos squamata), Blue-streaked Lory (E. reticulata), Red Lory (E. bornea), Rainbow Lorikeet (Trichoglossus haematodus), Chattering Lory (Lorius garrulus), Cockatail Australia (Nymphicus hollandicus), Moustached Parrakeet (Psittacula alexandri), Peach-faced Lovebird (Agapornis roseicollis), Fischer’s Lovebird (A. fischeri), Masked Lovebird (A. personata), Bali Hanging Parrot (Loriculus pusillus) and Budgerigar (Melopsittacus undulatus). The Rainbow Lorikeet was found more abundant than another species of parrots, but Bali or Javan Hanging Parrot was very rare. The most catching area of Psittacidae was about 45% from Moluccas Islands.